Making innovations work: local government–NGO partnership and collaborative governance in rural Bangladesh. Issue 1 (2nd January 2018) - Panday, Pranab
ABSTRACT: This article reports on a local government–NGO partnership in rural Bangladesh. The findings suggest that BRAC's Strengthening Local Governance initiative, through partnership with Union Parishads (the lowest tier of the existing local government structure), has been successful in strengthening the governance of Union Parishads by changing the mindsets of Union Parishad officials through building their capacity and mobilising people in the community to become involved in the Union Parishad's service delivery process. As a result, the service delivery process has been streamlined, corruption reduced, and accountability and transparency increased.